ANALISIS PERTUMBUHAN DAN PERGESERAN SRUKTUR EKONOMI KABUPATEN INDUK DI PROVINSI BENGKULU - Sunoto Sunoto; Bertha Iin Esti Indraswanti; Edy Rahmantyo Tarsilohadi (Convergence: The Journal of Economic Development, 2020)
The purpose of this research was to analyze economic growth and shifting of economic structure of the origin district in Bengkulu Province. Base on BPS secondary time series data (2001-2017), descriftive analysis was used to analyze economic growth and shifting economic structure, specialty after the region otonomous era (OTDA).  The DLQ and SSA method was used to determine the potential and leading sectors to increase economic performance. The result of this research was conclude that expansion of the the region in Bengkulu Provinsi has positif impact on economic development for the origin district. The economis structure was shifting from premier sector to secondary and tertier sector. The potential and leading sector after OTDA become more than before (from 4 or 5 sector to 7 untul 9 sector).  Keywords :  Dynamic Location Quotient 1, Shift Share Analysis 2, Economic Growth 3, Economic Structure 4, Potential and Leading Sector 5